Photocatalytic reduction of CO2 to methanol over ZnFe2O4/TiO2 (pân) heterojunctions under visible light irradiation - Iqbal, F. (John Wiley and Sons Ltd, 2020)
BACKGROUND: The development of visible light photocatalysts for CO2 reduction into methanol is a challenge, as most of the reported photocatalysts can only work in a UV light environment. Slow kinetics and poor selectivity of CO2 towards methanol are currently two significant drawbacks limiting the practical application of CO2 reduction into methanol. RESULTS: A ZnFe2O4/TiO2 heterojunction with a ratio of unity was found to lead to the highest methanol yield of 693.31 Î¼mol (g cat)â1 under a light intensity of 100 mW cmâ2. This photocatalyst also possessed the highest BET surface area of 6.5211 m2 gâ1 and better morphological structure, as compared with other ratios (1:2, 2:1 w/w). Interestingly, a loading of 1 g Lâ1 of ZnFe2O4/TiO2 (1:1) heterojunction photocatalyst in the pre-annealing treatment of ZnFe2O4 at 900 Â°C and post-annealing treatment of ZnFe2O4/TiO2 (1:1) composite at 500 Â°C revealed that there was an enhancement in the interfacial interaction, and subsequently an efficient photoreduction of CO2 into methanol. CONCLUSIONS: This study demonstrates facile fabrication of pân heterostructured phototcatalysts for reduction of CO2 with marked improvement in methanol yield under visible light irradiation. It provides a viable route for exploring the effects of composition, hydrothermal treatment, and pre-/post-annealing treatment of hybrid semiconductor composites used to scale up photocatalytic CO2 conversion in solar fuel-based devices. Â© 2020 Society of Chemical Industry